Design of early fault detection technique for electrical assets using infrared thermograms - Jaffery, Zainul Abdin; Dubey, Ashwani Kumar (International journal of electrical power & energy systems, 2014)
•Non Invasive Off Line Visual Inspection System (NIOLVIS) is developed.•Non Invasive Real Time Visual Monitoring System (NIRTVMS) developed.•Threshold based color segmentation technique is applied to detect hot regions.•An area based hotness detection algorithm is developed.•The systems (NIOLVIS) and (NIRTVMS) enhances the reliability of electrical assets. Infrared thermography is a non destructive temperature measuring technique, widely used in agriculture, process industries, manufacturing, pharmaceutical industries, and construction industries to detect anomalies, to predict possible faults, or to check the quality of the object. In this paper, two systems, real time and off line, are proposed to monitor the temperature variations and analyze hot regions in the electrical assets using infrared thermograms. This novel technique helps to prevent the electrical assets before any catastrophe would happen in the future. The color based segmentation technique is used to blotch hot regions in the thermograms of electrical systems. A redness area based algorithm is also proposed to analyze the hot regions and also to estimate rate of change of hotness in electrical assets for early detection and prediction of faults.